Thirteenth Annual ENBDC Workshop: Methods in Mammary Gland Biology and Breast Cancer - Twigger, Alecia-Jane; Sumbal, Jakub; Bentires-Alj, Mohamed; Howard, Beatrice A (Journal of mammary gland biology and neoplasia, 2022)
The thirteenth annual workshop of the European Network for Breast Development and Cancer (ENBDC) Laboratories Annual Workshop took place on the 28-30 April 2022 in Weggis, Switzerland and focused on methods in mammary gland biology and breast cancer. Sixty scientists participated in the ENBDC annual workshop which had not been held in person since 2019 due to the global COVID-19 pandemic. Topics spanned the mammary gland biology field, ranging from lactation biology and embryonic development, single cell sequencing of the human breast, and stunning cutting-edge imaging of the mouse mammary gland and human breast as well as breast cancer research topics including invasive progression of the pre-invasive DCIS stage, metabolic determinants of endocrine therapy resistance, models for lobular breast cancer, and how mutational landscapes of normal breast during age and pregnancy determine cancer risk. The latest findings from participating researchers were presented through oral presentations and poster sessions and included plenty of unpublished work.
Keywords: mléčné žlázy zvířat; pandemie; Humans; Mammary Glands, Animal; biologie; Female; Pandemics; lidé; zvířata; myši; Mammary Glands, Human; Mice; COVID-19; Breast Neoplasms; ženské pohlaví; Biology; nádory prsu; mléčné žlázy lidské; Animals